Meningkatkan Kinerja Karyawan melalui Disiplin Kerja, Pelatihan, dan Lingkungan Kerja di Rumah Sakit Umum Al-Islam H.M. Mawardi - Nur Indah Tirtasari; Vera Firdaus; Sumartik Sumartik (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This research is motivated by the importance of improving employee performance as a major factor in maintaining the quality of hospital services. The purpose of this study is to analyze the influence of work discipline, training, and work environment on employee performance at Al-Islam H.M. Mawardi General Hospital. This study uses a quantitative descriptive approach with a population of 220 employees and a sample of 142 respondents selected through a purposive sampling technique. Data were collected using a questionnaire and analyzed using the Partial Least Squares (PLS) method using SmartPLS 3.0 software. The results show that work discipline, training, and work environment have a positive and significant effect on employee performance. This indicates that improving discipline, implementing effective training, and creating a conducive work environment can strengthen work productivity and effectiveness. Therefore, hospital management is advised to prioritize maintaining these three factors to achieve optimal human resource performance.